Era uma vez... um carrossel: giros, paradas e metamorfoses de uma educadora - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present dissertation is the result of a research produced in the Professional Master's Degree program in Language Teaching (MPEL) at the Federal University of Pampa (UNIPAMPA), campus Bagé/RS, from January 2020 to March 2022. It consists of a proposal to work with the poetic text in nursery classes structured from the narration of my academic trajectory in the area of Languages and my performance as an attendant in an Early Childhood School of the Public Education Network in the municipality of Bagé/RS. The main objective of the research was, from my formative and professional experiences, to build a reading project with children's poetry of folk and contemporary origin, in order to contribute to the literary formation of babies, thus offering a pedagogical product aiming to educators working in early childhood education. As a theoretical foundation, I sought the concepts of Sahagoff (2015), Bondia (2002) and Castro (2020) in relation to the concepts of narrative research, which allowed me to reconstruct memories of my personal, academic and professional journey and reflect on my place as an educator graduated in the area of Languages working in early childhood education. I was based on Jean Piaget's (1999) and Vygotsky's (1991) considerations about the development process in the early stages of childhood. I investigated neuroscience and language studies in Parreiras (2012), Evelio Cabrejo-Parra (2011a), Howard Gardner (1994), Girotto; Souza; Balça (2019), Concenza & Guerra (2011) and in Cunha (2018). On the issues of literature, children's poetry and childhood, brought concepts from Bordini (1991) and (2010), Juan Cervera (1992), Yolanda Reyes (2010), Jesualdo Sosa (1976) and Evelio Cabrejo-Parra (2011b). The basis for the construction of the methodology of the poetic project “Cadê você, uni, duni, tê?” were studies by Girotto and Souza (2015) and Silva (2019), which deal with embryonic reading gestures and their four dimensions. The project is organized in didactic sequences with activities that include three thematic units: self-knowledge, knowledge of the world and projection in the figure of another. This proposal is materialized in an educational product in the form of a didactic manual, which is attached to this dissertation, and a website aimed at professionals working in early childhood education. As a final result of this research, I emphasize that I was able to reflect, from the reconstruction of my memories about my true role as an educator, and to propose a pedagogical product with children's poetry plausible to be explored in nursery classes.
Keywords: Pesquisa narrativa; Poesia infantil; Berçário; Educação infantil; Gestos embrionários de leitura; Narrative research; Children's poetry; Nursery; Child education; Embryonic gestures of reading; CNPQ::LINGUISTICA, LETRAS E ARTES